2011
DOI: 10.1371/journal.pone.0024585
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Carbohydrate Digestion and Transport and Mucosal Dysbiosis in the Intestines of Children with Autism and Gastrointestinal Disturbances

Abstract: Gastrointestinal disturbances are commonly reported in children with autism, complicate clinical management, and may contribute to behavioral impairment. Reports of deficiencies in disaccharidase enzymatic activity and of beneficial responses to probiotic and dietary therapies led us to survey gene expression and the mucoepithelial microbiota in intestinal biopsies from children with autism and gastrointestinal disease and children with gastrointestinal disease alone. Ileal transcripts encoding disaccharidases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
376
3
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 420 publications
(399 citation statements)
references
References 96 publications
11
376
3
9
Order By: Relevance
“…In fact, the distal small intestine (ileum) harbored a greater richness of bacteria on the mucosa compared with the lumen. (Savage, 1987) proposed that the mucosal bacterial populations in the gut both stabilize the intestinal community and prevent pathogens by providing a constant, established inoculum for the lumen to complete the breakdown of non-digested food substrates (Williams et al, 2011). Perhaps the mucosal bacteria of the ileum serve as an inoculum for the large intestine.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the distal small intestine (ileum) harbored a greater richness of bacteria on the mucosa compared with the lumen. (Savage, 1987) proposed that the mucosal bacterial populations in the gut both stabilize the intestinal community and prevent pathogens by providing a constant, established inoculum for the lumen to complete the breakdown of non-digested food substrates (Williams et al, 2011). Perhaps the mucosal bacteria of the ileum serve as an inoculum for the large intestine.…”
Section: Discussionmentioning
confidence: 99%
“…41 Several studies have now reported changes in microbiota profile in patients with autism. [41][42][43][44][45][46][47] While this area of research is new and consensus across studies has not yet been established, several interesting observations are worth noting. In one recent study, an increased diversity of microbiota was observed in patients with severe autism compared with matched controls; and in particular Bacteroidetes was significantly increased in patients with autism, whereas Firmicutes was observed to be higher in controls.…”
Section: Effects Of the Central And Peripheral Nervous Systems On Thementioning
confidence: 99%
“…47 In contrast, another study that compared patients with autism and GI problems (ASD + GI) to patients with GI problems alone, showed reduced Bacteroidetes and increased Firmicutes and Betaproteobacteria (Sutturela) presence in ASD + GI patients. 43 It also has been speculated that secretion of bacterial (neuro) toxins produced by clostridia may affect behavior and stress in autistic subjects. 45 Furthermore, urinary metabolite phenotypes-mostly derived from gut bacterial fermentation-differentiated children with autism from their unaffected microbiota in alleviating anxiety-like behaviors.…”
Section: Effects Of the Central And Peripheral Nervous Systems On Thementioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported the prevalence of GI problems, one of common comorbid conditions of ASD [83,84]. Accumulat-ed findings lead to the hypothesis of gut-brain axis, which suggests that gut microbiota can alter brain activity through endocrinal, metabolic or immunological mechanisms, and can possibly induce the pathogenesis of ASD [85][86][87][88].…”
Section: Gastrointestinal Microbiota In Asdmentioning
confidence: 99%